Role for Target of Rapamycin (mTOR) Signal Pathway in Regulating Neuronal Injury after Intracerebral Hemorrhage - Wang, Jie-Ping; Zhang, Meng-Yu (Cellular physiology and biochemistry, 2017)
Background/Aims: Mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase and activation of its signal pathway plays an important role in regulating protein growth and synthesis as well as cell proliferation and survival. In the present study, we examined the contribution of mTOR signal and its downstream products to brain injuries induced by intracerebral hemorrhage (ICH) in rats. Methods: Western Blot analysis was employed to examine the protein expression of mTOR and its downstream pathway and Caspase-3. ELISA was used to measure pro-inflammatory cytokines (PICs) and vascular endothelial growth factor (VEGF). Additionally, neurological Severity Score and brain water content were used to indicate neurological function and brain edema. Results: The protein expression of p-mTOR, mTOR-mediated phosphorylation of 4E–binding protein 4 (4E-BP1), p70 ribosomal S6 protein kinase 1 (S6K1) pathways were amplified in ICH rats compared with controls. Blocking mTOR using rapamycin significantly attenuated upregulation of PICs, namely IL-1β, IL-6 and TNF-α, and Caspase-3 indicating cell apoptosis, and promoted the levels of VEGF and its subtype receptor VEGFR-2 in brain tissues. Moreover, the effects of rapamycin were linked to improvement of neurological deficits and increased brain water content observed in ICH rats. Conclusion: Activation mTOR signal is engaged in pathophysiological process during ICH and blocking mTOR pathway plays a beneficial role in regulating neuronal tissues via PIC, apoptotic Caspase-3 and VEGF mechanisms. This has pharmacological implications to target specific mTOR and its downstream signal pathway for neuronal dysfunction and vulnerability related to ICH.